Evaluation of Education Administrators’ Technological Leadership Competencies and Their Perceptions of the Use of the Metaverse in Education - Perihan Mafratoğlu; Zehra Altinay; Recepali Mafratoğlu; Ahmet Koç; Fahriye Altinay; Gökmen Dağli (SAGE Open)
School principals play a key role in integrating schools into the digital age. Hence, this research aimed to evaluate education administrators’ technological leadership competencies and their perceptions of the use of the metaverse in education. The study adopted a simultaneous parallel mixed method design. Survey modeling was used in the quantitative research phase, and phenomenology was used in the qualitative phase. Three hundred and sixty four principals participated in the quantitative research and 17 participated in the qualitative part. The research findings indicate that school principals possess a high level of technology leadership competencies and perceptions regarding the use of the metaverse in education and that there is a low-level positive and statistically significant relationship between the participants’ technology leadership competencies and their perceptions of the metaverse in education. While there is consistency between the quantitative and qualitative data, an inconsistency was found concerning the dimensions of digital citizenship and knowledge levels related to the metaverse. Further, although consistency between the quantitative and qualitative data was generally observed, there was inconsistency regarding the principals’ digital citizenship and level of knowledge and awareness regarding the metaverse, the implication of which can researched in depth in future. Based on this study’s findings, education administrators should be supported with pre- and in-service training to develop their skills in using and managing technology.